Lower protein expression levels of MHC class I chain-related gene A in hepatocellular carcinoma are at high risk of recurrence after surgical resection. Issue 1 (December 2018) - Huang, Chung-Feng; Wang, Shu-Chi; Chang, Wen-Tsan; Yeh, Ming-Lun; Huang, Ching-I; Lin, Zu-Yau; Chen, Shinn-Cherng; Chuang, Wan-Long; Huang, Jee-Fu; Dai, Chia-Yen; Chen, Yao-Li; Yu, Ming-Lung
Abstract MHC class I chain-related gene A (MICA) variants have been associated with hepatocellular carcinoma (HCC). Their association with MICA expression in cancer cells and cancer recurrence is unknown. SNP rs2596542 of MICA was tested in 193 HCC patients with surgical resection. The corresponding MICA expression in the cancer tissue was measured by immunochemistry microarray. Patients with the SNP rs2596542 A allele had significantly lower MICA expression in tumor tissue than did those with the GG genotype (24.7 ± 15.1% vs. 41.5 ± 23.4%, P < 0.001). Patients who had HCC recurrence had significantly lower MICA expression in tumor tissue (34.2 ± 21.8% vs. 24.0 ± 19.8%, P = 0.03). Cox regression analysis revealed that the factors independently predictive of HCC recurrence included low MICA expression (hazard ratio [HR]/95%confidence intervals [CI]: 2.77/1.07–7.14, P = 0.035) and tumor size (HR/CI: 5.22/2.11–12.96, P < 0.001). Compared to patients with tumors <5 cm and MICA expression >30%, patients with either one and both two risk factors had HCC HRs of 9.76 (C.I. 1.27–75.03, P = 0.03) and 27.30 (C.I. 3.46–215.6, P = 0.002), respectively. We concluded that low cellular MICA expressions were at a greater risk of HCC recurrence after curative treatment.